2009
DOI: 10.1590/s0103-84782009000100018
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural morphology and morphometry of the normal corneal endothelium of adult crossbred pig

Abstract: Corneal endothelium constitutes a monolayer of polygonal cells. The integrity and health of this layer are essential for the maintenance of normal corneal transparency. This study reported by the first time in a detailed RESUMO O endotélio corneal é uma monocamada de células poligonais. A integridade e saúde dessa camada são essenciais para a manutenção da transparência corneal normal. Este estudo reportou pela primeira vez, de forma detalhada, a morfologia ultra-estrutural e a morfometria do endotélio corneal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
37
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 18 publications
4
37
1
2
Order By: Relevance
“…The results observed in this study show that normal swine corneal endothelium consisted of a continuous monolayer with mainly hexagonal cells, but were also found cells with five sides and with seven sides. Previous studies conducted involving vertebrate animals have shown that there is predominance of cells with hexagonal shape and, in lower proportion, there is presence of five-and seven-sided cells (Collin & Collin, 1998, Pigatto et al 2005, Gum et al 2007, Tamayo-Arango et al 2009, Bercht et al 2015, Coyo, et al 2015.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…The results observed in this study show that normal swine corneal endothelium consisted of a continuous monolayer with mainly hexagonal cells, but were also found cells with five sides and with seven sides. Previous studies conducted involving vertebrate animals have shown that there is predominance of cells with hexagonal shape and, in lower proportion, there is presence of five-and seven-sided cells (Collin & Collin, 1998, Pigatto et al 2005, Gum et al 2007, Tamayo-Arango et al 2009, Bercht et al 2015, Coyo, et al 2015.…”
Section: Discussionmentioning
confidence: 97%
“…This methology has also been used with excellent results in previous studies (Pigatto et al 2005, Franzen et al 2010, Coyo et al 2015. SEM has been widely used to compare the endothelial ultrastructure of vertebrates, and to evaluate the effects of medication, chemicals or surgical procedures on the endothelium (Pigatto et al 2005, Tamayo-Arango et al 2009). …”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations